Бісерний декор ансамблю українського народного одягу: стан дослідження проблеми - Федорчук, О. (Інститут народознавства НАН України, 2008)
The tradition of using glass beads to decorate national garments among Ukrainians — superimposed adornments and beading upon the clothes — had been a subject matter for art critics and ethnographers. Literature analysis of this issue enabled us to look at the tradition of beading in Ukrainian national art from different angles. After centuries of formation and development, Ukrainian tradition encountered a number of changes. Historiographic research shows us that beadwork occupied a large temporal and territorial gap in both Ukrainian and European culture and formed an outstanding phenomenon of Ukrainian art. It has also turned out that artistic and stylistic distinctions of beadwork in Ukrainian national garments are yet to be studied.